The Use of Sequence Picture to Improve the Students’ Speaking Skill At SMK Negeri 1 Sei Kepayang - Dewi Wulandari*; Cici Handayani; Sharina Amanda (Universitas Syiah Kuala, 2023)
This research aimed to improve the students’ speaking skill by using the sequence pictures. Classroom action research constituted the method used in this research which was conducted at SMK Negeri 1 Sei Kepayang, Asahan. The research data was obtained by conducting the research for the tenth grade students of SMK Negeri 1 Sei Kepayang which consists of 25 students. The data was analyzed as quantitative and qualitative. The quantitative result showed that there were 76% students who had better English for speaking after using the sequence pictures as the learning media in learning English. Meanwhile, the students’ motivation and interest for learning English was increasing. It was as the qualitative data. Therefore, it can be concluded that the use of sequence pictures as the media learning in English subject was effective to increase the students’ speaking skill for the tenth grade students at SMK Negeri 1 Sei Kepayang, Asahan. It is suggested for the English teacher to use this media to improve the students’ speaking skill for English subject.